2018
DOI: 10.5205/1981-8963-v12i11a234770p3046-3051-2018
|View full text |Cite
|
Sign up to set email alerts
|

Análise de vídeos sobre hiv/aids e adolescência

Abstract: Objective: to analyze videos posted about HIV/AIDS and adolescence in the YouTube channel and its implications on the practice of care. Method: this is a quantitative, exploratory study using a sample of 137 videos using the descriptors "adolescent, infection, HIV, Aids, videos" using the Boolean operator and. The content was categorized for the discussion of the data and the analysis of the final sample. Results: the power of influence that the media can generate and the aspects that directly influence the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
5
0
4
Order By: Relevance
“…A Agência Nacional de Saúde Suplementar [25] ressalta a importância do acesso à educação em saúde para a população, pois a implementação do conhecimento gera como benefícios, além da qualidade de vida do indivíduo, o fato de proporcionar ao mesmo a possibilidade de ser um multiplicador de informações ajudando na melhoria de sua localidade regional. Outra questão importante é a construção do conhecimento sabendo respeitar as origens socioculturais da região e acrescentar o saber popular a este processo, facilitando o entendimento dos indivíduos envolvidos e a efetividade da proposta, tendo como desafio a quebra de paradigmas sem que este afete a adesão do conhecimento [26,27].…”
Section: Discussionunclassified
“…A Agência Nacional de Saúde Suplementar [25] ressalta a importância do acesso à educação em saúde para a população, pois a implementação do conhecimento gera como benefícios, além da qualidade de vida do indivíduo, o fato de proporcionar ao mesmo a possibilidade de ser um multiplicador de informações ajudando na melhoria de sua localidade regional. Outra questão importante é a construção do conhecimento sabendo respeitar as origens socioculturais da região e acrescentar o saber popular a este processo, facilitando o entendimento dos indivíduos envolvidos e a efetividade da proposta, tendo como desafio a quebra de paradigmas sem que este afete a adesão do conhecimento [26,27].…”
Section: Discussionunclassified
“…Initially, the search for the present theme was carried out in order to verify if there were articles published previously using the same methodological path or close to what would be developed and that also described the possibility of visualizing some previous study on herpes virus types 1 and 2. Thus, studies were identified on: adolescence and HIV 21 and one on an online video contest about the destigmatization of herpes virus infection 22 , being that this last one was not an analysis realized with videos published in the Portuguese language. In this way the option was to carry out an exploratory analysis.…”
mentioning
confidence: 99%
“…It is also emphasized that the virtual platform chosen for the accomplishment of these postings has free access and, in this research, the comments of the participants and their criticisms were not evaluated, thus not requiring submission to the Research Ethics Committee (REC), as well as in previously published studies. 21,23 Thus, two examiners began the search using the following keywords, starting from the definition of Descriptors in Health Sciences (DeCS): human herpes virus 1; human herpes virus 2; ulcer; infection; STD. These descriptors were crossreferenced to each other by the use of the term "AND".…”
mentioning
confidence: 99%
See 2 more Smart Citations